Memory of representation of social life in the explanation of Al- zouzni for the sleepless seven - Mebirik, Mohammed Yamani (Arab Journal for Sciences and Research Publishing, 2020)
This study dealt with a critical approach to explaining pendants, and chose to stand on its social side, with a descriptive approach, which revealed the links between modern criticism and ancient criticism. Reading was a procedural tool for research, and It started to develop hypotheses as temporary solutions that permeate its interlocutors and infiltrated its features with the function of projection and convergence. Where I reached the features of social study according to this vocabulary: writing, charters, medicine, banking, Transportation, adornment, cooking, ritual, construction, etc.
Keywords: Study; Criticism; Social Life; Approach; Methodology